My Mother, My Mirror - Ong, You Ling (Nanyang Technological University, 2023)
"My Mother My Mirror" is a non-fiction narrative that explores the societal effects of mother wound trauma on women through a deep dive into the real-life stories shared by daughters as they reflect on their lives and challenging relationships with their mothers.